2020
DOI: 10.1055/s-0040-1715613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Strategies on the Development of Fulminant Necrotizing Enterocolitis

Abstract: Introduction Necrotizing enterocolitis (NEC) causes significant neonatal morbidity. A subset of infants experience precipitous decline and death from fulminant-NEC (F-NEC). We sought to determine the effect of feeding practices on the development of this more virulent form of NEC. Materials and Methods Premature neonates developing Bell's stage II or III NEC between May 2011 and June 2017 were reviewed. Infants were stratified as having NEC or F-NEC, defined as NEC-totalis or NEC causing rapid declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…In this cohort, the age at NEC onset seemed to be higher in the RP-NEC group than in the nRP-NEC group, but this did not reach statistical significance (10 [6, 20] vs. 8 [4,16], p = 0.053). In agreement with our study, Yu et al presented a study showing that a severe condition had a tendency for a later age of onset (10 [7.5, 22.25] vs. 7 [2,14], p = 0.4) (10). However, an earlier age of disease onset for severe NEC has been widely illustrated.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this cohort, the age at NEC onset seemed to be higher in the RP-NEC group than in the nRP-NEC group, but this did not reach statistical significance (10 [6, 20] vs. 8 [4,16], p = 0.053). In agreement with our study, Yu et al presented a study showing that a severe condition had a tendency for a later age of onset (10 [7.5, 22.25] vs. 7 [2,14], p = 0.4) (10). However, an earlier age of disease onset for severe NEC has been widely illustrated.…”
Section: Discussionsupporting
confidence: 93%
“…Of the non-surviving NEC patients, some died from a rapid course, called fulminant NEC, which was considered a sub-category condition. Fulminant NEC accounts for 6.7%-28% of the entire NEC population and is associated with a high mortality rate of 95.7%-100% (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study of 80 infants with medical or surgical NEC reported an overall mortality of 36%; however, the mortality in 23 infants with pan-intestinal necrosis was 96%. 19 This extremely high mortality rate confirms the severity of the disease and underscores the need for more research into primary prevention and early recognition of NEC to reduce the risk of fulminant disease.…”
Section: Discussionmentioning
confidence: 70%